Trauma History and Social Support Among American Indian/Alaska Native and Non-Native Survivors of Intimate Partner Violence - Burrage, Rachel L. (Journal of interpersonal violence, 2021)
Social support (SS) is one of the most important protective factors against the deleterious effects of trauma exposure on mental health, but only a few studies have looked at predictors of SS among trauma-exposed populations. This study examines what predicts SS from friends, family, and other significant individuals in an ethnically diverse group of 61 women residing in Alaskan shelters for women who have experienced Intimate Partner Violence (IPV). Results from bivariate tests indicated that survivors who identified as American Indian or Alaska Native (AIAN) reported significantly higher SS from family (M = 5.04, SD = 1.74) in comparison with those who do not identify as AIAN (M = 3.80, SD = 2.31), t(56) = 2.24, p < .05. Income was positively correlated with higher SS from friends, r(59) = .33, p < .05. Lifetime history of interpersonal trauma was significantly and negatively related to variation in SS across multiple domains. When sociodemographic variables, trauma history, and violent relationship history were entered into a multiple regression, this model predicted 34% (p < .001) of the variance in Overall SS and 22% (p < .01), 32% (p < .001), and 17% (p < .05) of SS from family, friends, and other significant individuals, respectively. Taken together, these preliminary results suggest that income, race, lifetime interpersonal trauma history, and number of violent partners are important predictors of SS among women IPV survivors residing in shelters.